Directory of photographers in Belgium 1839-1905 : volume 2 : album - Joseph, Steven F.; Schwilden, Tristan; Claes, Marie-Christine (Antwerpen: C. de Vries-Brouwers, 1997)
"Steven F. Joseph, Tristan Schwilden, Marie-Christine Claes ; Museum voor Fotografie. Antwerp"